[Attendees gathered hand in hand at Multicultural Center dedication], January 15, 1982 (1982)
Attendees gathered, holding each other's hands, in the University Union plaza, just outside the campus bookstore. Banners for campus events hang from the Union's second-story balcony, including one for an AIAA meeting.